2014
DOI: 10.2146/ajhp130489
|View full text |Cite
|
Sign up to set email alerts
|

Automated preparation of chemotherapy: Quality improvement and economic sustainability

Abstract: Both the automated and manual procedures for preparing antineoplastic preparations proved to be accurate and precise. The automated procedure resulted in substantial advantages in terms of quality maintenance standards and risk lowering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 16 publications
(14 reference statements)
3
64
0
1
Order By: Relevance
“…Seger et al 7 showed that mean drug preparation time increased by 47% on using a fully automated robotic approach compared with manual compounding. Even if we also assessed a slightly shorter time consumption for a comparable manual process (about 66 min), we see several advantages in using a robotic device as already described recently:8 The assessed time consumption refers to one person working at the device, whereas the manual volumetric-based preparation is strictly bound to two persons for safety reasons (number of materials in the working area, in process-cross-checks). Staff can take care of preprocessing and postprocessing steps for recent and future runs while the production run is being performed automatically.…”
Section: Discussionmentioning
confidence: 96%
“…Seger et al 7 showed that mean drug preparation time increased by 47% on using a fully automated robotic approach compared with manual compounding. Even if we also assessed a slightly shorter time consumption for a comparable manual process (about 66 min), we see several advantages in using a robotic device as already described recently:8 The assessed time consumption refers to one person working at the device, whereas the manual volumetric-based preparation is strictly bound to two persons for safety reasons (number of materials in the working area, in process-cross-checks). Staff can take care of preprocessing and postprocessing steps for recent and future runs while the production run is being performed automatically.…”
Section: Discussionmentioning
confidence: 96%
“…From January to August 2015, the median rate of absolute dose error more than 5% was 0.7% (range: 0.0–1.9%) for each month in the robotic preparation (total of 3,192 preparations for 34 anticancer drugs) in practice. There is one report comparing the performance between robotic preparation using APOTECAchemo and manual preparation, showing that both preparations were accurate and precise [12]. The range of percent dose error (accuracy) and standard deviation (precision) for robotic preparation were from −3.71 to 0.42% and from 0.57 to 1.92%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the compounding robot APOTECAchemo (Loccioni Humancare, Italy) has been used in 51 hospitals in 14 countries [11, 12]. Robotic preparation leads to solve the problem of manual preparation, such as exposure or contact of hazardous drugs, stress of preparation, human error of preparation, and weakness of traceability for preparation error.…”
Section: Introductionmentioning
confidence: 99%
“…These robots reduce the occupational exposure of health care workers during the compounding process, yet like the other options, are not perfect, most of all because they require human staff to load and clean and most of the time they do not give a quick performance. They are generally more expensive and do not substantially reduce serious medication errors [29, 30]. …”
Section: Primary Engineering Controlmentioning
confidence: 99%